2021
DOI: 10.1111/bcp.14833
|View full text |Cite
|
Sign up to set email alerts
|

Drug–drug interactions with warfarin: A systematic review and meta‐analysis

Abstract: The objective of this paper is to systematically review the literature on drugdrug interactions with warfarin, with a focus on patient-important clinical outcomes.Methods: MEDLINE, EMBASE and the International Pharmaceutical Abstract (IPA) databases were searched from January 2004 to August 2019. We included studies describing drug-drug interactions between warfarin and other drugs. Screening and data extraction were conducted independently and in duplicate. We synthesized pooled odds ratios (OR) with 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 106 publications
(415 reference statements)
1
40
0
2
Order By: Relevance
“…Predicting optimal warfarin dose is influenced by many factors including demographic, clinical, environmental, and genetic factors, and multiple drug interactions, such as age, weight, height, vitamin K epoxide reductase complex subunit 1 (VKORC1) genotype, cytochrome P450 family 2 subfamily C member 9 (CYP2C9) genotype, coadministration of antiplatelet drugs, antimicrobials, nonsteroidal anti-inflammatory drugs (NSAIDs), and proton pump inhibitors, etc. [ 3 , 4 , 5 , 6 , 7 ]. Therefore, a tailored warfarin dose may help clinicians to select the appropriate dose for individualized warfarin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting optimal warfarin dose is influenced by many factors including demographic, clinical, environmental, and genetic factors, and multiple drug interactions, such as age, weight, height, vitamin K epoxide reductase complex subunit 1 (VKORC1) genotype, cytochrome P450 family 2 subfamily C member 9 (CYP2C9) genotype, coadministration of antiplatelet drugs, antimicrobials, nonsteroidal anti-inflammatory drugs (NSAIDs), and proton pump inhibitors, etc. [ 3 , 4 , 5 , 6 , 7 ]. Therefore, a tailored warfarin dose may help clinicians to select the appropriate dose for individualized warfarin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…7 Gastrointestinal bleeding (GIB) risk is one of the most serious adverse effects of warfarin, which could be affected by the concomitant use of other drugs that influence the effect of warfarin through reduction of gastrointestinal absorption of warfarin or inhibition of cytochrome P450 (CYP) enzymes (particularly CYP2C9, which is responsible for metabolizing the more potent warfarin enantiomer). 7 Among drugs that could increase the risk of bleeding when taken along with warfarin are antiplatelets, antimicrobials such as azole antifungals, cephalosporins, sulfonamides, penicillins and quinolones, opioid analgesics, and nonsteroidal anti-inflammatory drugs. [7][8][9] Recent evidence from multiple individual studies examining the association between use of statins and the risk of GIB reported conflicting findings, [10][11][12][13] with variable risks reported relative to duration of statin exposure.…”
Section: Introductionmentioning
confidence: 99%
“…7 Among drugs that could increase the risk of bleeding when taken along with warfarin are antiplatelets, antimicrobials such as azole antifungals, cephalosporins, sulfonamides, penicillins and quinolones, opioid analgesics, and nonsteroidal anti-inflammatory drugs. [7][8][9] Recent evidence from multiple individual studies examining the association between use of statins and the risk of GIB reported conflicting findings, [10][11][12][13] with variable risks reported relative to duration of statin exposure. [14][15][16] Thus, whereas the risk of GIB among users of warfarin is well known, 5 there is a lack of conclusive evidence about the GIB risk associated with the use of statins alone or in combination with warfarin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations